The APOA5 rs662799 polymorphism is associated with dyslipidemia and the severity of coronary heart disease in Chinese women. Issue 1 (December 2016) - Wang, Yanmei; Lu, Zhan; Zhang, Jingxiao; Yang, Yang; Shen, Jing; Zhang, Xiaoming; Song, Yongyan
Abstract Background TheAPOA5 rs662799 polymorphism has been widely reported regarding its associations with the plasma lipid levels and the occurrence of coronary heart disease (CHD), whereas its relationship with the severity of CHD has not yet been explored. Methods Four hundred and seventy-eight angiografically defined subjects (325 CHD patients and 153 CHD-free controls) were enrolled in this study. The rs662799 polymorphism was genotyped, and the fasting lipid data were collected for all participants. The severity of CHD was evaluated for the CHD patients by using Gensini scores. Results The variant C allele of the rs662799 polymorphism was associated with lower levels of HDL-C in CHD-free women, and higher levels of TG and TG/HDL-C in women with CHD (P < 0.05 for all). The C allele was associated with higher prevalence of dyslipidemia and higher levels of Gensini scores only in women (P < 0.05 for both), but not in men. Multivariate linear regression analysis showed that the rs662799 polymorphism was independently associated with the Gensini scores in women after adjustment for other potential CHD risk factors (Beta = 0.157, 95 % CI: 0.017–0.298, P = 0.028). Conclusion Our data indicate that the rs662799 polymorphism is associated with dyslipidemia and the severity of CHD in Chinese women.